Declining water yield from forested mountain watersheds in response to climate change and forest mesophication - Peter V. Caldwell; Chelcy F. Miniat; Katherine J. Elliott; Wayne T. Swank; Steven T. Brantley; Stephanie H. Laseter (Global Change Biology, 2016)
Climate change and forest disturbances are threatening the ability of forested mountain watersheds to provide the clean, reliable, and abundant fresh water necessary to support aquatic ecosystems and a growing human population. Here, we used 76 years of water yield, climate, and field plot vegetation measurements in six unmanaged, reference watersheds in the southern Appalachian Mountains of North Carolina, USA to determine whether water yield has changed over time, and to examine and attribute the causal mechanisms of change. We found that annual water yield increased in some watersheds from 1938 to the mid‐1970s by as much as 55%, but this was followed by decreases up to 22% by 2013. Changes in forest evapotranspiration were consistent with, but opposite in direction to the changes in water yield, with decreases in evapotranspiration up to 31% by the mid‐1970s followed by increases up to 29% until 2013. Vegetation survey data showed commensurate reductions in forest basal area until the mid‐1970s and increases since that time accompanied by a shift in dominance from xerophytic oak and hickory species to several mesophytic species (i.e., mesophication) that use relatively more water. These changes in forest structure and species composition may have decreased water yield by as much as 18% in a given year since the mid‐1970s after accounting for climate. Our results suggest that changes in climate and forest structure and species composition in unmanaged forests brought about by disturbance and natural community dynamics over time can result in large changes in water supply.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Long-Term Forest Ecosystem Research: A Programmatic View - Wayne T. Swank; James M. Vose (Journal of Forestry, 2009)

Long-term changes in forest composition and diversity following early logging (1919–1923) and the decline of American chestnut (Castanea dentata) - Katherine J. Elliott; Wayne T. Swank (Plant Ecology, 2008)

Long-Term Soil Responses to Site Preparation Burning in the Southern Appalachians - Jennifer D. Knoepp; James M. Vose; Wayne T. Swank (Forest Science, 2004)
The mixed oak–pine ecosystems in the southern Appalachians are in decline because of a combination of drought and southern pine-beetle infestation. A commonly applied prescription for restoration of these degraded sites has been to fell all vegetation, allow it to dry, and conduct a site-preparation burn. However, there is little information on the mid- and long-term influences of this prescription on nutrient cycling. The fell-and-burn treatment was applied to three mixed oak–pine stands in the Nantahala National Forest in western North Carolina. Each stand had an untreated control area. Our objective was to determine the effects of this treatment on soil nutrient availability and potential nutrient loss. Exchangeable soil cations, pH, total carbon (C), and total nitrogen (N) were measured before and periodically for 5 years after treatment. Nitrogen transformations and nutrient availability in soil solution and in a stream draining one site were measured before and periodically for 3 years after burning. Exchangeable calcium and magnesium concentrations, soil pH, and N availability increased after treatment. There was no treatment effect on total soil C or N. Nitrogen mineralization rates were greater on burned versus control plots in 50% of the posttreatment measurements. This treatment increased nutrient availability and, although a significant amount of total site N was lost, there were no adverse effects on total soil nutrients or water quality. FOR. SCI. 50(4):540–550.

Hillslope Nutrient Dynamics Following Upland Riparian Vegetation Disturbance - J. Alan Yeakley; David C. Coleman; Bruce L. Haines; Brian D. Kloeppel; Judy L. Meyer; Wayne T. Swank; Barry W. Argo; James M. Deal; Sharon F. Taylor (Ecosystems, 2003)

Using soil temperature and moisture to predict forest soil nitrogen mineralization - Jennifer Knoepp; Wayne Swank (Biology and Fertility of Soils, 2002)

Rates of nitrogen mineralization across an elevation and vegetation gradient in the southern Appalachians - Jennifer D. Knoepp; Wayne T. Swank (Plant and Soil, 1998)